2005
DOI: 10.1002/dc.20343
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphology of gastric and duodenal epithelium and reactivity to B72.3: A baseline for comparison to pancreatic lesions aspirated by EUS-FNAB

Abstract: Endoscopic ultrasound-guided fine-needle aspiration biopsy (EUS-FNAB) has become a widely used method of pre-operatively evaluating pancreatic masses. This technique introduces gastrointestinal contamination into the specimen, which poses a diagnostic pitfall. The cytomorphologic features of these contaminants have not been fully characterized. The current study was designed to systematically document the cytomorphology of gastric and duodenal epithelium on fixed and air-dried smears, as well as ThinPrep (TP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 7 publications
(4 reference statements)
1
21
0
Order By: Relevance
“…12,16,17 The difficulty in interpreting degenerated cells in cyst fluid, coupled with the concern for over interpretation of gastrointestinal contamination, typically results in a conservative cytologic interpretation. 18,19 In addition, HGD and malignant cells associated with invasive carcinoma often have the same degree of cytologic atypia. Therefore, many cytopathologists-especially cytopathologists who have little experience interpreting pancreatic cyst fluids-elevate the threshold for a malignant interpretation and may undervalue the significance of small clusters of cells with atypia but no overt features of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…12,16,17 The difficulty in interpreting degenerated cells in cyst fluid, coupled with the concern for over interpretation of gastrointestinal contamination, typically results in a conservative cytologic interpretation. 18,19 In addition, HGD and malignant cells associated with invasive carcinoma often have the same degree of cytologic atypia. Therefore, many cytopathologists-especially cytopathologists who have little experience interpreting pancreatic cyst fluids-elevate the threshold for a malignant interpretation and may undervalue the significance of small clusters of cells with atypia but no overt features of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Only complicated cases with gastrointestinal epithelial and mucin contamination, particularly from the stomach, should include cystic lining epithelial cells. [19,21,22] Van der Waaij et al analyzed 12 studies and demonstrated that CEA levels below 5 ng/mL present a specificity of 95% for pseudocyst formation. [18] Biliary complications of PPs manifest as obstructive jaundice, requiring intervention until the pseudocyst resolves.…”
Section: Discussionmentioning
confidence: 99%
“…10). 67 Atypical epithelial cells are most critical to recognize, as we have shown that these cells even when very scant correlate with an increased risk of malignancy. 12,62,79 A neoplastic mucinous cyst with a cyst lining of moderate or higher dysplasia may produce atypical epithelial cells in small, tight, bud-like clusters or singly with increased nuclear to cytoplasmic ratio, irregular nuclear membranes, and cytoplasm with or without mucin (Fig.…”
Section: Cancer Cytopathologymentioning
confidence: 96%
“…66 Gastrointestinal epithelial and mucin contamination, particularly from the stomach, can lead to a misdiagnosis of a mucinous cyst. 65,67,68 Special stains for mucin that show only scant amounts of mucin-positive fluid should not be interpreted as evidence of a mucinous neoplasm, as this finding may well represent gastrointestinal contamination. Cyst fluid analysis with an elevated amylase in the thousands and low CEA level (<192 ng/mL) supports the interpretation of a pseudocyst.…”
Section: Pseudocystmentioning
confidence: 99%
See 1 more Smart Citation